Pattern of hospitalized-stroke patients in ASEAN countries an ASNA stroke epidemiological study (Faculty of Medicine Universitas Indonesia, 2001)
To better understanding the demographic characteristics, admission time, clinical pattern, risk factors, stroke type, length of stay, and discharge outcome of hospitalized acute stroke patients in ASEAN member countries, ASEAN Neurological Association (ASNA) formed a Standing Commiltee for Stroke in 1996 and this is the first ASNA Stroke Epidemiological Study using the same stroke protocol. This prospective hospital based study was conducted in seven ASEAN countries (Brunei, Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam) by participating neurologists from October 1996 to March 1997. Of the 3723 consecutive hospitalized stroke patients (2030 males and 1660 females) from 44 participating hospitals in this study ie Brunei (n=53), Indonesia (n=2065), Malaysia (n=300),Philippines (n=545),Singapore (n=232), Thailand (n=244) and Vietnam (n=284), the mean age was 59.0±13,8 years 16% of patients were younger than 45 years and 37% of patients were older than 65 years. There were no significant differences in age at onset among stroke subjects except in Vietnam (younger) and Singapore (older). The sex distribution showed a slight higher prevalence of women in Singapore and in the age group > 64 years. The mean adrnission time was 41.5± 87.0 hours, 19% of patients were admitted within 3 hours, 29% within 6 hours and 66% more than 6 hours (delayed admission) especially in Malaysia and Singapore (80% and 77% respectively). Motor disability was the most prevalent clinical feature in all countries and carotid bruit was the rarest (1%). Hypertension was the most common risk factor (68%) in all countries, followed by TIA (35%), smoking, diabetes mellitus, ischnemic heart disease and hypercholesterolemia. CT scan was performed on 76% of subjects. The diagnostic classification was non lacunar anterior circulation (32%), lacunar infarction (14%), hemorrhagic stroke (26%), SAH (4%). Mean length of stay was 11.4±11.8 days. Most of the patients discharged from the hospital were alive improved (57%) and mean death rate was 22%, highest in Thailand (45%) and lowest in Brunei (8%). This hospital based stroke data showed the recent characteristics of stroke pattern in seven ASEAN member countries and it will be very important data for health policy maker in these countries and for further cooperative researches in the future. (Med J Indones 2001; 10: 48-56) Keywords: Stroke, clinical pattern, risk factor